2011
DOI: 10.1161/hypertensionaha.111.172114
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 10 Deficiency Exacerbates Toll-Like Receptor 3–Induced Preeclampsia-Like Symptoms in Mice

Abstract: Abstract-Preeclampsia may result from overactivation of the maternal immune system and is characterized by endothelial dysfunction and excessive inflammation. Given the importance of maternal immune system regulation and antiinflammatory cytokines in normotensive pregnancies, we hypothesized that maternal immune system activation via Toll-like receptor 3 during pregnancy would cause preeclampsia-like symptoms in mice, which would be made worse by deficiency of the anti-inflammatory cytokine interleukin 10. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
90
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(95 citation statements)
references
References 51 publications
3
90
0
2
Order By: Relevance
“…However, TLR3, TLR7, and TLR8 have all been associated with maternal hypertension in rodent models with preeclampsia-like symptoms (Tinsley et al, 2009;Chatterjee et al, 2011Chatterjee et al, , 2012Chatterjee et al, , 2013Chatterjee et al, , 2015Ishimoto et al, 2013;Kopriva et al, 2013). Moreover TLR7/8, as well as TLR9, from SHR splenocytes evoked the greatest proinflammatory responses to angiotensin II when primed with their respective exogenous ligands (Harwani et al, 2012).…”
Section: B Hypertensionmentioning
confidence: 99%
“…However, TLR3, TLR7, and TLR8 have all been associated with maternal hypertension in rodent models with preeclampsia-like symptoms (Tinsley et al, 2009;Chatterjee et al, 2011Chatterjee et al, , 2012Chatterjee et al, , 2013Chatterjee et al, , 2015Ishimoto et al, 2013;Kopriva et al, 2013). Moreover TLR7/8, as well as TLR9, from SHR splenocytes evoked the greatest proinflammatory responses to angiotensin II when primed with their respective exogenous ligands (Harwani et al, 2012).…”
Section: B Hypertensionmentioning
confidence: 99%
“…On the other hand, George et al [17] found that induction of TLR3 led to [55] demonstrated that activation of TLR3 led to the expression of pro-inflammatory cytokine IL-6 and chemokine MCP-1 in human coronary VSMCs. Group of Mitchell found that maternal hypertension (i.e., preeclampsia) developed in TLR3 agonist-treated animals [45,11,12]. Therefore, a comprehensive understanding of the role of TLR3 in cells of the vasculature including VSMCs is imperative.…”
Section: Discussionmentioning
confidence: 99%
“…These results lead us to speculate that sustained TLR3 activation can enhance vascular contraction. Chatterjee et al [11] found that TLR3 agonist (Poly I:C) led to endothelial dysfunction, hypertension, and proteinuria in pregnant mice (treatment with Poly I:C, 20 mg/kg, i.p., on days 13, 15, and 17 of pregnancy), but not in nonpregnant mice. Our current study identifies a significant role of TLR3 in male mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The interaction between the maternal endothelium and activated peripheral blood leukocytes [23] would further reduce, or cross, the threshold for the development of clinical preeclampsia [24]. Several studies have shown that TLR3 activation during pregnancy causes preeclampsia-like symptoms indicating that TLR3 plays a key role in the development of PE [25][26][27].…”
Section: Discussionmentioning
confidence: 99%